Assessment of systemic stress in patients undergoing third molar surgery: use of in situ cortisol levels as an indicator - Huamán Mujica, Karina (2025)
Objective: To determine in situ serum cortisol levels in patients undergoing third molar surgery. Materials and methods: The study population consisted of patients from the University-Teaching Hospital of Chimbote (Hospital Universitario-Docente de Chimbote), who were selected based on inclusion and exclusion criteria. The sample consisted of 30 patients, from whom blood samples were taken at three different times (pre-, intra-, and post-operative) to determine serum cortisol levels using the ELISA technique. The values were transferred to a database and processed using descriptive statistical analysis (mean and standard deviation) and inferential analysis (Kruskal-Wallis and Tukey's tests). Results: Preoperatively, 66.7% (n = 20) of patients had serum cortisol levels within the normal range (50-230 ng/mL), while 33.3% (n = 10) had levels above 230 ng/mL. Intraoperatively, 60% (n = 18) of patients presented cortisol levels higher than 230 ng/mL, and postoperatively, this was observed in 56.7% (n = 17). A statistically significant increase in serum cortisol was found intraoperatively (285.53 ± 108.00 ng/mL) compared to preoperative values (198.00 ± 74.85 ng/mL), and this elevated level was sustained in the postoperative period (280.67 ± 113.09 ng/mL), although no statistically significant difference was observed between intra- and postoperative values. Conclusion: The present work reports significant in situ increases in serum cortisol levels due to the physiological alteration caused by surgical trauma, mantained until the post-operative period.